Genetic properties of bla CTX-M, bla SHV and bla TEM genes in ESBL producing E. coli clinical isolates - Akhvlediani, Leila (Journal of Medical Care Research and Review, 2021)
Extended-spectrum β-lactamase (ESBL) producing Escherichia coli is a serious global public health problem that requires timely and accurate control of resistant strains. This is the first report on the detection of resistant E. coli isolates in hospitals of Adjara. We studied the genetic profile of Escherichia coli isolates producing ESBL isolated from biological samples of patients with suspected nosocomial infection in four hospitals in the Adjara region (Georgia). Identification of resistant genes was performed by multiplex PCR and reverse hybridization. Genes of the class ESBL TEM, ESBL SHV, and CTX-M were found in these samples as a result of molecular studies of genes causing genotypic correlation and resistance. Molecular genetic testing of phenotypically resistant strains of penicillin, cephalosporins of the 3rd and 4th generations, and inhibitors revealed a wide range of antibiotic resistance genes with bla CTX-M, bla TEM, bla SHV, and in two samples with genes, of ESBL class bla TEM type mutated genes: bla TEM AS104 E, bla TEM AS 238 G, bla TEM AS238 S genes.